Reported restorative experiences associated with everyday activities among university students. (October 2019) - Atler, Karen E; Sharp, Julia
Introduction: Increasing international concern about the mental health of university students continues to rise, as they are among those at great risk for experiencing stress. Yet little research exists on the role of activity engagement as a means to renew resources often impacted by stress. This study aimed to explore university students' restorative experiences associated with everyday activities. Method: Data were gathered from 264 students, using a stress scale and time-use assessment. Students' activity descriptions were coded into 20 activity types. A hierarchical linear mixed effects statistical model was employed to estimate the average restoration by activity types. Results: No significant differences were found in average restoration within activity types between high and low stress categories. Sleeping was the most restorative activity reported. However, the mean restoration value of sleeping did not significantly differ from eight other activities, such as reading and engaging in a hobby. Working was the least restorative activity, and did not differ from five other activities such as studying and attending class. Restorative experience varied more among some activities, such as engaging in a hobby and caring for the home, than others, such as sleeping and caring for self. Conclusion: University students' report of some everyday activities being as restorative as sleep offers support for the use of occupation by occupational therapists, enabling students to learn how to manage their energy needs through everyday occupations.